Fostering Creative Thinking in Early Learners through STEAM-Based Ecoprint Projects - Jazariyah, Jazariyah; Athifah, Nur Zahra; Purnamasari, Yayu Mega; Lita (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This research investigates the impact of integrating STEAM (Science, Technology, Engineering, Arts, and Mathematics) project-based learning (PjBL) with Ecoprint activities on developing creative thinking skills in early childhood. A mixed-methods concurrent embedded design was adopted, focusing on preschool children aged 4-6 years from two educational institutions in Karangsari Village, Cirebon District. The study engaged 30 participants in Ecoprint activities, utilizing natural materials to create prints on paper and fabric. These activities were framed within the STEAM PjBL methodology, encompassing stages of Reflection, Research, Discovery, Application, and Communication to facilitate a comprehensive earning experience. Qualitative data, collected through interviews with educators and observations of the Ecoprint projects, were complemented by quantitative assessments of the children's development of creative thinking skills. This dual approach allowed for a rich, multifaceted analysis of the learning processes and outcomes. The creative thinking abilities of the participants were evaluated using a standardized rating scale aligned with criteria set forth by the Ministry of Education and Culture, tracking progress from initial baselines to post-intervention stages. The findings indicate a notable enhancement in creative thinking among the children, with a significant majority advancing from lower levels of creative dev. Children can select and sort the base color materials from the collected leaves. At this stage, the potential of STEAM PjBL, combined with hands-on, environmentally focused artistic activities like Ecoprint, is to enrich early childhood education by fostering creative, innovative thinking. The study's implications extend to curriculum development, advocating for including interdisciplinary, experiential learning strategies that blend scientific inquiry with artistic creativity. However, the research is limited by its scope and its participants' demographic and geographic characteristics. Future studies are recommended to explore the scalability of this approach and its long-term impacts across diverse educational settings, potentially offering valuable insights into the role of integrated STEAM education in nurturing holistic cognitive development in young learners.